Developing knowledge creation capability: The role of big-five personality traits and transformational leadership - Malik Umer Ayub; Fizza Kanwal; Abdul Rashid Kausar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Current research aims to develop and test a conceptual framework that poses attention to individuals' personality as a potential predictor of their knowledge creation capability, considering the mediating effect of transformational leadership. According to an estimate, poor knowledge management costs Fortune 500 companies' huge annual losses through taking a toll on their efficiency and productivity. Thus knowledge management is crucial for organizations, and various ways to improve knowledge creation and management need to be studied. In this regard, current research uses Nonaka's knowledge creation theory to study the knowledge creation capability in organizations as a consequence of managers' personality and leadership style. Cross-sectional data was collected from middle level managers working in thirteen different organizational sectors from Pakistan. Covariance based structural equation modeling was used to test hypotheses. All scales were found reliable; however, measurement models were re-specified to improve the construct validity. Through SEM, this research revealed that openness, agreeableness and extraversion have direct influence on knowledge creation capability. Furthermore, transformational leadership mediates the relationship between all the Big-Five personality traits and knowledge creation capability. Therefore, to develop knowledge creation capability of managers, organizations should rethink their organizational procedures to put in place such recruitment, selection, and training & development practices that are oriented towards managers' personalities and their leadership styles. To the best of our knowledge, this is the first study that identifies Big-Five personality traits as antecedents of knowledge creation capability, incorporates transformational leadership in the model, and tests these relationships empirically. It also provides valuable insights in the domain of knowledge management among middle level managers of various Pakistani firms.
Keywords: 330; knowledge creation capability; openness to new experience; agreeableness; conscientiousness; extraversion; neuroticism; big-five personality traits; transformational leadership